Pengaruh Aaktivitas Permainan Olahraga Terhadap Peningkatan Kebugaran Jasmani Siswa Smkn 10 Garut - Gumilar, Gumilar; Hadi Kosasih, Alam; Arifin, Z. (Jurnal Speed (Sport, Physical Education, Empowerment), 2024)
This increase in physical fitness is a must in the learning process. Physical fitness not only has a good effect on the development of affective aspects in students, but good physical fitness can also have an effect on student learning outcomes. This problem is based on the lack of aspects of physical fitness (endurance, muscle endurance, and speed). The method used in this research is experimental research. This study used a type of experimental research, namely the pre-experimental design with the One Group Pretest-Posttest Design (Ali Maksum, 2012). Based on the results of the t test, it is known that the pre-test average is 1.5 after being given physical education and sports treatment in 16 meetings, the post-test value is 3.31 so it is known that the increase is 1.75. Furthermore, based on the t-test, the t-count value is 12.124. The t-table value with a df of 25 at a significant level of 5% is 0.144. Therefore t-count > t-table (12.124 > 0.144) and the significance value is smaller than 0.05 (0.00 <0.05) so that it can be stated that there is a significant increase in the score of physical fitness results by being given physical education and exercise during 16 meetings, description, testing of research results, and discussion, it can be concluded that there is an influence of physical education and exercise on physical fitness